Bright Aggregation‐Induced‐Emission Dots for Targeted Synergetic NIR‐II Fluorescence and NIR‐I Photoacoustic Imaging of Orthotopic Brain Tumors. Issue 29 (28th May 2018) - Sheng, Zonghai; Guo, Bing; Hu, Dehong; Xu, Shidang; Wu, Wenbo; Liew, Weng Heng; Yao, Kui; Jiang, Jingying; Liu, Chengbo; Zheng, Hairong; Liu, Bin
Abstract: Precise diagnostics are of significant importance to the optimal treatment outcomes of patients bearing brain tumors. NIR‐II fluorescence imaging holds great promise for brain‐tumor diagnostics with deep penetration and high sensitivity. This requires the development of organic NIR‐II fluorescent agents with high quantum yield (QY), which is difficult to achieve. Herein, the design and synthesis of a new NIR‐II fluorescent molecule with aggregation‐induced‐emission (AIE) characteristics is reported for orthotopic brain‐tumor imaging. Encapsulation of the molecule in a polymer matrix yields AIE dots showing a very high QY of 6.2% with a large absorptivity of 10.2 L g −1 cm −1 at 740 nm and an emission maximum near 1000 nm. Further decoration of the AIE dots with c‐RGD yields targeted AIE dots, which afford specific and selective tumor uptake, with a high signal/background ratio of 4.4 and resolution up to 38 µm. The large NIR absorptivity of the AIE dots facilitates NIR‐I photoacoustic imaging with intrinsically deeper penetration than NIR‐II fluorescence imaging and, more importantly, precise tumor‐depth detection through intact scalp and skull. This research demonstrates the promise of NIR‐II AIE molecules and their dots in dual NIR‐II fluorescence and NIR‐I photoacoustic imaging for precise brain cancer diagnostics. Abstract : c‐RGD‐decorated aggregation‐induced‐emission (AIE) dots are developed to show bright NIR‐II fluorescence with strong NIR‐I absorptivity, good biocompatibility, and excellent photostability, and offer precise orthotopic brain‐tumor diagnosis via synergetic NIR‐II fluorescence and NIR‐I photoacoustic imaging with deep penetration, high spatial resolution, and good signal‐to‐background ratio.